A dynamic analysis approach for identifying the elastic properties of unstitched and stitched composite plates. (15th September 2016) - Li, Nan; Ben Tahar, Mabrouk; Aboura, Zoheir; Khellil, Kamel
Abstract: The identification of elastic properties from the dynamic behavior of structure has long been an alternative method to mechanical test. This method can avoid the variability of properties due to extraction of the specimen and achieve better homogenization by involving the whole structure. The mode classification is proposed and integrated in the identification process in this paper and helps to reduce the calculation time. Firstly, the measured frequencies are provided by vibration test while the calculated frequencies are provided by a finite element model with discrete Kirchhoff plate element. Then a mode classification process is conducted to accelerate the identification. Every constant is identified by minimizing the difference between the calculated and the measured frequencies of the group that it dominates. This method has been applied to two types of composite plate: unstitched plate and dispersedly stitched plate which presents both macro and meso heterogeneity. The limited dimension along the width direction of the stitch makes the modulus inaccessible by mechanical test and thus this dynamic method turns to be indispensable.